Cooking of the dried mushrooms as an effective solution for the reduction of the 137Cs concentration - Kseniya V. Varfolomeeva (Радиационная гигиена)
The aim of the current study was to evaluate the effectiveness of cooking (washing, soaking and boiling) of the mushrooms to reduce the 137Cs concentration. The following tubular dried mushrooms were selected for the study: Boletus edilus (cepe), porcini lurid boletus, annulated boletus, orange-cup boletus, variegated boletus and bay bolete. The mushrooms were collected in 2016 in the Bryansk region areas (Gordeevsky, Klintzovsky and Krasnogorskiy districts) with the maximum contamination after the Chernobyl NPP accident. The activity concentration of 137Cs was determined by gamma-spectrometry. Effectiveness of cooking was assessed by calculating the coefficient of cooking reduction equal to the ratio of the activity of 137Cs in water fraction to the activity in the initial dried mushroom sample. The results of the study indicated that the most effective way of cooking the mushrooms was washing, allowing reducing the concentration of 137Cs by 49%. The major part of 137Cs was transferred to the water fraction with the first decanting – 32%; with the consecutive two decantings – 11% and 6%, respectively. During the soaking of mushrooms, 26% of 137Cs is transferred into the water fraction within the first 3 hours: 14% – during the first hour, 9% – in the second and 3% – in the third. Increase in the soaking time had low effect on the reduction of the concentration of 137Cs and reduced the taste characteristics of the meal. The complex use of all three stages of cooking (washing, soaking and boiling) allows reducing the concentration of 137Cs up to 75% in the mushroom broth.